Implementation of Deep Learning-Based Gamification in Strengthening Islamic Cultural History Literacy at MAN Lima Puluh - Listari Basuki; Ficki Padli Pardede (Pusdikra Publishing, 2026)
Islamic Cultural History (SKI) learning in digital classrooms still tends to emphasize memorization, generate boredom, and use technology in ways that do not yet fully encourage historical meaning-making. This study aims to analyze the implementation of deep learning-based gamification in strengthening SKI literacy in the X-2 Digital class at MAN Lima Puluh, Batu Bara Regency. The study employed a qualitative approach with a single-case study design. Informants were purposively selected from the SKI teacher and students. Data were collected through classroom observations, semi-structured interviews, and documentation in the form of teaching modules, gamification media, assignments, and students’ reflections; the data were then analyzed thematically through condensation, display, and conclusion drawing and verification. Data credibility was maintained through source and technique triangulation and confirmation with informants. Preliminary findings indicate that the integration of points, badges, leaderboards, levels, challenges, and feedback can organize the learning process from factual mastery toward cause-and-effect analysis, contextual meaning-making, communication of results, and reflection on historical lessons (ibrah). Gamification supports meaningful, mindful, and joyful learning when rewards are given for the quality of arguments, contributions, answer revisions, and collaboration, rather than only for speed or ranking. However, individual leaderboards, network limitations, an orientation toward pursuing points, and weak evaluation of source credibility can limit the depth of literacy. The novelty of the study lies in the operational integration of gamification elements, three deep learning principles, and four dimensions of SKI literacy. These findings emphasize the need for inclusive, reflective, and source-based gamification design.